ANALISIS DUKUNGAN MASYARAKAT UNTUK PENGEMBANGAN PARIWISATA BERKELANJUTAN - Rahman, Budi; Ariyanto, Edi; Sari, Delfia Tanjung (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2024)
Tourism will develop if the views of local communities are taken into account in the tourism development process itself. Therefore, understanding tourism development from the perspective of local communities will deepen understanding of the long-term success of tourist destinations. This research aims to understand community support for tourism development based on social exchange theory and Bottom Up Spillover using primary data obtained through distributing questionnaires to communities around tourist attractions. The number of respondents was 200 people. The analytical tool used is SEM PLS. The research results found theoretical and empirical evidence about the relationship between variables. Based on the structural equation model, it shows that the benefits felt by residents from tourism development have a positive effect on satisfaction with material and non-material life domains, thus this will contribute to the overall quality of life. Then overall quality of life is an effective predictor to support tourism development.